RANCANG BANGUN APLIKASI PENJADWALAN MATA PELAJARAN SMK BERBASIS WEB PADA SMK BINA INFORMATIKA (BINTER) TERNATE - Farhan Diaz Pramudya (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2022)
SMK Bina Informatika (BINTER) Ternate still uses a manual system in the process of scheduling subjects in each semester, indeed in the process of making assistance with Information Technology media, namely computers, but here it is only as an auxiliary tool used for writing and structuring the schedule so that the schedule can be made with quickly and quickly then can be reproduced also the schedule of subjects that have been so. Web-Based Vocational Subject Scheduling Application Design at SMK Bina Informatika (Binter) Ternate. Made using the php and mysql programming languages, this application is made simple and easy to use. Based on the results of the trial program for now it can run well so that it can be used to convey information about the lesson schedule at SMK Bina Informatika (BINTER) Ternate.